Democratic System Strengthening Through Concurrent Election Implementation To Improve Political Stability and National Development - Tjenreng, Muhammad Baharuddin Zubakhrum (Journal of Social and Development Sciences, 2016)
Indonesian recently held a regional head concurrent elections in the first phase on December 9, 2015. Concurrent elections has been a historic moment for Indonesia to elect regional heads organized and structured massively. Concurrent election significance for Indonesian politics, especially at the local level, not only to read limited local democratic party, but rather an instrument for strengthening the democratic process. This research seeks to examine and analyze the democracy strengthening through concurrent election implementation in order to improve political stability of national development. In carrying out this study, researchers using qualitative methods. Whereabout the main data from this study is the researchers observation result on the concurrent election day, which is supported by several secondary data from the media. Featured models concurrent election (local concurrent election) is believed to be the best solution to counter the problems remaining in the elections execution, especially in two important reasons: First, the elections implementation effectiveness in order to realize the elections are more qualified and dignified from both the process and elections outcome aspects; second, the elections efficiency especially from the budget efficiency aspect which must be issued by the state to finance the electoral process.